2004
DOI: 10.1073/pnas.0308035101
|View full text |Cite
|
Sign up to set email alerts
|

NFAT is a nerve activity sensor in skeletal muscle and controls activity-dependent myosin switching

Abstract: Calcineurin (Cn) signaling has been implicated in nerve activitydependent fiber type specification in skeletal muscle, but the downstream effector pathway has not been established. We have investigated the role of the transcription factor nuclear factor of activated T cells (NFAT), a major target of Cn, by using an in vivo transfection approach in regenerating and adult rat muscles. NFAT transcriptional activity was monitored with two different NFATdependent reporters and was found to be higher in slow compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
200
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(210 citation statements)
references
References 40 publications
9
200
0
Order By: Relevance
“…Swoap et al (37) concluded from in vitro and in vivo studies that CaN and NFAT are not sufficient to dictate the slow muscle program, consistent with our previous analysis of the TnI SURE (15,27). On the other hand, McCullagh et al (36) showed that transcription from an artificially trimerized IL-2 NFAT site is selectively enhanced by slow-patterned activity, a finding we have reproduced here (Fig. 6A).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Swoap et al (37) concluded from in vitro and in vivo studies that CaN and NFAT are not sufficient to dictate the slow muscle program, consistent with our previous analysis of the TnI SURE (15,27). On the other hand, McCullagh et al (36) showed that transcription from an artificially trimerized IL-2 NFAT site is selectively enhanced by slow-patterned activity, a finding we have reproduced here (Fig. 6A).…”
Section: Discussionsupporting
confidence: 91%
“…6A). Consistent with previous reports (36,37), expression of the 3xNFAT construct was Ϸ3-fold higher in the soleus than EDL muscles (soleus, 272% Ϯ 23% vs. EDL, 100% Ϯ 25%). NFATc1 knockdown significantly reduced transcription of the 3xNFAT reporter in the soleus (soleus, 272% Ϯ 23% vs. soleus ϩ NFATc1 siRNAs, 117% Ϯ 11%, P Ͻ 0.05) but had no effect in transfected EDL muscle (EDL, 100% Ϯ 25% vs. EDL ϩ NFATc1 siRNAs, 93% Ϯ 21%).…”
Section: Sirna-mediated Knockdown Of Nfatc1 Reduces the Repression Ofsupporting
confidence: 92%
See 2 more Smart Citations
“…Calmodulin activation through binding to calcium promotes an increase in calcinueurin A activity, which has been shown to result in the exclusion of NFAT from the nucleus, to subsequently increase the activity of MEF2 and drive a slow-type fiber switch. PGC-1α has also been shown to coactivate MEF2 to promote a transition toward oxidative fiber types, a process that is thus likely to be potentiated through the PGC-1α-dependent induction of HIF2α (41)(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%